Self-reported beta-lactam allergy and the risk of surgical site infection: A retrospective cohort study. (23rd April 2020) - Lam, Philip W.; Tarighi, Payam; Elligsen, Marion; Gunaratne, Keith; Nathens, Avery B.; Tarshis, Jordan; Leis, Jerome A.
Abstract: Objective: To assess whether a self-reported β-lactam allergy is associated with an increased risk of surgical site infection (SSI) across a broad range of procedures and to determine whether this association is mediated by the receipt of an alternate antibiotic to cefazolin. Design: Retrospective cohort study. Participants: Surgical procedures sampled by an institutional National Surgical Quality Improvement Program database over an 18-month period (January 2017 to June 2018) from 7 surgical specialties. Setting: Tertiary-care academic hospital. Results: Of the 3, 589 surgical procedures included in the study, 369 (10.3%) were performed in patients with a reported β-lactam allergy. Those with a reported β-lactam allergy were significantly less likely to receive cefazolin (38.8% vs 95.5%) or metronidazole (20.3% vs 26.1%) and were more likely to receive clindamycin (52.0% vs 0.2%), gentamicin (3.5% vs 0%), or vancomycin (2.2% vs 0.1%) than those without allergy. An SSI occurred in 154 of 3, 220 procedures (4.8%) in patients without reported allergy and 27 of 369 (7.3%) with reported allergy. In the multivariable regression model, a reported β-lactam allergy was associated with a statistically significant increase in SSI risk (adjusted odds ratio [aOR], 1.61; 95% confidence interval [CI], 1.04–2.51; P = .03). This effect was completely mediated by receipt of an alternate antibiotic to cefazolin (indirect effect aOR, 1.68; 95% CI, 1.17–2.34; P = .005). Conclusions: Self-reported β-lactam allergy was associated with an increased SSI risk mediated through receipt of alternate antibiotic prophylaxis. Safely increasing use of cefazolin prophylaxis in patients with reported β-lactam allergy can potentially lower the risk of SSIs. Abstract :